Hypoglycemia-Induced Hemiparesis in a Diabetic Woman after Childbirth - Vera Kukaj; Fisnik Jashari; Dren Boshnjaku; Enis Istrefi; Pranvera Ibrahimi (Case Reports in Neurological Medicine)
A 24-year-old female with type 1 diabetes mellitus presented with hemiparesis induced by hypoglycemia. She was hospitalized because she has noticed a weakness of her right hand and leg three days after childbirth. On physical examination she had an expressive dysphasia and right side hemiparesis with facial drop. Hypoglycemia is rarely associated with hemiparesis and it is often overlooked, especially when it happens in patients at higher risk of other diseases frequently associated with hemiparesis. Although sporadical cases of hypoglycemia-induced hemiparesis were reported, the clear pathophysiology behind this is not well determined. However, any individual case is important in order to increase the awareness of hypoglycemia as an important etiology of this condition.